Potential effect of beetroot juice supplementation on exercise economy in well-trained females - Forbes, S. P. A.; Spriet, L. L. (Applied Physiology, Nutrition, and Metabolism, 2022)
This study examined if acute dietary nitrate supplementation (140 mL beetroot juice, BRJ) would reduce oxygen consumption (V?O2) during cycling at power outputs of 50 and 70% maximal oxygen consumption in 14 well-trained female Canadian University Ringette League athletes. BRJ had no effect on V?O2 or heart rate but significantly reduced ratings of perceived exertion (RPE) at both intensities. Individually, 4 participants responded to BRJ supplementation with a =3% reduction in V?O2 at the higher power output.